Worldviews in Collision: Jesus as Critical Educator - Newell, Ted (Journal of education & Christian belief, 2009)
CONTEMPORARY CONNOTATIONS OF “teacher” don't do justice to Jesus' educating activity. “Worldview” understood as a comprehensive social environment helps us to perceive the scale of Jesus' struggle in his society and also Christian teachers' struggle in their settings. Jesus is Israel's teacher in a deeper way than we hear by the term “teacher.” Perspectives opened up by New Testament scholarship's Third Quest for the historical Jesus show that Jesus aimed to clarify the true meaning of God's covenant with Israel while subverting the dominant worldview. The argument is illustrated by analogy with another worldview challenger, the Italian Marxist Antonio Gramsci, who developed strategies to counter what he named “hegemony.” I conclude with implications for Christian teachers: teachers should understand themselves to be enacters of Jesus' way with students in Christian school or state school settings.